2018
DOI: 10.3389/fpsyg.2018.00337
|View full text |Cite
|
Sign up to set email alerts
|

Negative Transfer Effects on L2 Word Order Processing

Abstract: Does first language (L1) word order affect the processing of non-canonical but grammatical syntactic structures in second language (L2) comprehension? In the present study, we test whether L1-Spanish speakers of L2-Basque process subject–verb–object (SVO) and object–verb–subject (OVS) non-canonical word order sentences of Basque in the same way as Basque native speakers. Crucially, while OVS orders are non-canonical in both Spanish and Basque, SVO is non-canonical in Basque but is the canonical word order in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 77 publications
0
13
1
Order By: Relevance
“…Learners do not only have to learn the L2 rule but need to simultaneously inhibit their L1, which may fail in the early stages of L2 learning, thus leading to reversed processing signatures. Although such reversed processing signatures have been reported before for cross-linguistically incompatible grammatical gender (Bultena, Danielmeier, Bekkering, & Lemhöfer, 2017;Lemhöfer et al, 2014) and word order (Erdocia & Laka, 2018), we did not find evidence for such a reversed P600 effect. The L1 bias was thus either not strong enough or had already been overcome.…”
Section: N400-like Signatures As Markers Of Low L2 Proficiencycontrasting
confidence: 83%
See 1 more Smart Citation
“…Learners do not only have to learn the L2 rule but need to simultaneously inhibit their L1, which may fail in the early stages of L2 learning, thus leading to reversed processing signatures. Although such reversed processing signatures have been reported before for cross-linguistically incompatible grammatical gender (Bultena, Danielmeier, Bekkering, & Lemhöfer, 2017;Lemhöfer et al, 2014) and word order (Erdocia & Laka, 2018), we did not find evidence for such a reversed P600 effect. The L1 bias was thus either not strong enough or had already been overcome.…”
Section: N400-like Signatures As Markers Of Low L2 Proficiencycontrasting
confidence: 83%
“…The few studies that examined how L2 learners deal with such conflicts have shown that word order differences in L1 and L2 remain difficult even at high proficiency levels and when the L2 was learned early on in life (Erdocia & Laka, 2018;Erdocia, Zawiszewski, & Laka, 2014). In both of these studies, learners' online processing signatures showed clear evidence of L1 Spanish influence on parsing L2 Basque sentences.…”
Section: Introductionmentioning
confidence: 98%
“…Marinis et al, 2005;Papadopoulou and Clahsen, 2003). Zawiszewski et al (2011) suggest a possible transfer of processing routines from L1 Spanish in processing Basque structures as an explanation for the differing performance of non-native participants on the grammatically diverging phenomena such as word order (see also Erdocia and Laka, 2018). 4 Our results corroborate this line of literature, by showing a non-native behavior in Region 5 and postverbal regions (9-11) in the clitic manipulation, although our non-native participants did detect the respective anomaly concerning clitic placement at one point, namely, the verb, in Italian.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary material for this article is available online Notes 1 Under this generalization, the difference in L2 online processing between speakers of two overt wh-movement languages such as Spanish and German, discussed in the text, could possibly be attributed to further grammatical factors which affect processing, for instance, canonical word order (SVO in Spanish, SOV in German). See also Zawiszewski et al (2011) and Erdocia and Laka (2018). 2 A related type of cost-reducing efficiency principle suggested in the literature is Minimality, which states that "in the absence of explicit information to the contrary, the human language comprehension system assigns minimal structures" (Bornkessel andSchlesewsky 2009:1542).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The constraints that guide comprehension may differ in their relative weighting and/or timing, and, as I argue below, differences in processing performance between populations might reflect between-population differences in constraint weightings, or differences regarding the point in time at which an information source affects processing decisions. Non-native language processing may additionally be influenced by linguistic properties of comprehenders' native or prior languages (e.g., Erdocia & Laka, 2018), as well as by maturational constraints. That is, the age at which the L2 has been acquired may affect whether or not L2 comprehenders can demonstrate native-like processing performance (see Birdsong, 2018, for a review and discussion).…”
Section: Constraint Interaction In Language Comprehensionmentioning
confidence: 99%